Assessment of Babesia ovis pathogenicity in goats: implications for transmission dynamics and host resistant - Ozubek, Sezayi; Ulucesme, Mehmet Can; Suarez, Carlos E.; Bastos, Reginaldo G.; Aktas, Munir (Frontiers Media Sa, 2024)
Babesia ovis, commonly associated with ovine babesiosis, poses a significant threat to sheep health, often resulting in severe clinical manifestations and high mortality rates. However, the impact of B. ovis on goats has remained uncertain, prompting us to investigate its pathogenicity in caprine hosts. Experimental infections using B. ovis-infected blood inoculation and infected tick infestation, were conducted on spleen-intact (n=5) and splenectomized (n=5) goats. The experimental infection was performed using fresh blood obtained from a B. ovis-infected splenectomized sheep. One spleen-intact sheep served as a control for the experimental infection with B. ovis-infected Rhipicephalus bursa ticks. While all experimentally infected sheep (#501, #575) displayed severe clinical symptoms and high parasitemia, goats exhibited resistance, showing no significant clinical manifestations or sustained parasitemia. Notably, B. ovis was detected in two spleen-intact goats via nested PCR, prompting further investigation into their role as reservoirs for tick-borne transmission. These goats were then infested with Babesia spp.-free R. bursa larvae (0.1 gr) and adults (50 females and 50 males) for transstadial and transovarial transmission experiments respectively. Results indicated that chronically B. ovis-infected spleen-intact goats are not significant sources for maintaining the tick-borne transmission cycle of the parasite. These findings highlight the differential susceptibility of goats to B. ovis infection compared to sheep and their limited role as reservoirs for parasite transmission. Understanding the role of goats in B. ovis transmission and their resistance mechanisms can inform effective control measures and reduce economic losses in affected regions. Further research into caprine babesiosis and host immunological responses is essential to fully elucidate their possible role as reservoirs of the parasite, and underlying mechanisms of host susceptibility and parasite pathogenesis.
Keywords: Babesia ovis; experimental infection; goat; pathogenicity; Rhipicephalus bursa